KAJIAN KESIAPSIAGAAN MASYARAKAT TERHADAP BENCANA TSUNAMI DI DESA LEMBONGAN, BALI - I Made Pacung Oka Widnyana; I Komang Gede Santhyasa; Komang Ayu Sari Galih (Pranatacara Bhumandala: Jurnal Riset Planologi, 2022)
Lembongan Village, Lembongan Island, and Ceningan Island are on the list of villages with a high class tsunami danger, disaster preparedness is important to prevent or cope with tsunami natural disasters and to limit losses and risks caused by tsunami disasters. The goal of this research is to establish the level of community preparedness in Lembongan Village for a tsunami disaster, as well as the link between the variabels of tsunami preparedness in Lembongan Village. The benefits of this research are for local governments in terms of preparedness and solutions so that tsunami disaster mitigation becomes integrated, coordinated, and comprehensive in order to minimize potential tsunami losses, for villages in terms of additional information and insight to increase coastal community preparedness for tsunami disasters, and for communities in terms of material for consideration in disaster mitigation actions, especially community preparedness. The study method employs a descriptive approach with a quantitative approach that supports qualitative data gathering using questionnaires, interviews, and field observations, as well as scoring analysis tools and MICMAC analysis. The study's findings show that 1) Lembongan Village's level of community readiness for a tsunami disaster is in class 2, with criteria of "Medium" or "Almost Ready". 2) The direct influence of the knowledge and attitude (KA) and Policy Statement (PS) factors on other variabels is significant. Meanwhile, knowledge and attitude (KA) and Policy (PS) variabels have a significant impact on variabels like emergency planning (EP), Warning System (WS), and Resource Mobilization Capacity (RMC).